2022
DOI: 10.24911/ijmdc.51-1631971689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression among hypertensive patients: a systematic review

Abstract: Hypertension is the elevation in the blood pressure level, and it is responsible for cardiovascular diseases. Depression and anxiety diseases are the most common mental disorders globally. Depression is common among patients with chronic disorders, including hypertension, and there are conflicts regarding the correlation between hypertension and anxiety. To assess the prevalence of anxiety and depression among hypertensive patients. PubMed and Google Scholar databases were searched for articles on the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar findings were obtained by AlKhathami's research, which had a 38.4% anxiety rate as measured by the GAD-7 scale, wherein mild anxiety accounted for 65.5%, moderate anxiety for 23%, and severe anxiety for 11.5% [5]. A meta-analysis of anxiety rates in hypertension patients in Somaili's study found a range of 4.1% to 42.3% [6]. However, we discovered a discrepancy with the study of author Le Minh Hoang (2022), when anxiety levels were 55.22% [7].…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings were obtained by AlKhathami's research, which had a 38.4% anxiety rate as measured by the GAD-7 scale, wherein mild anxiety accounted for 65.5%, moderate anxiety for 23%, and severe anxiety for 11.5% [5]. A meta-analysis of anxiety rates in hypertension patients in Somaili's study found a range of 4.1% to 42.3% [6]. However, we discovered a discrepancy with the study of author Le Minh Hoang (2022), when anxiety levels were 55.22% [7].…”
Section: Discussionsupporting
confidence: 83%